Factores de adopción y retención de CMMI: revisión sistemática de la literatura - Alfaro Ponte, Francisco Eduardo; Silva Obregon, Cynthia Lizeth (Pontificia Universidad Católica del Perú, 2023)
CMMI has increased the productivity and reduced the cost of software development in the software industry. However, there are factors that influence the adoption and retention of CMMI in software organizations, and that need to be studied over time. This article aims to identify factors that influence the adoption and retention of CMMI in the software development organizations. A systematic literature review (SLR) was performed for this study. In the first stage, 2507 articles were obtained from 6 relevant databases and after the SLR process, 40 studies on factors and their possible influence were selected. These factor studies were classified according to a taxonomy based on: organization, people, processes and product. The most studied factors are related to people and organizations, in the CMMI adoption and retention processes, which is consistent with the fact that it is the "people" of the software development "organizations" who manage to carry out the software projects. Studies related to retention factors are still scarce, representing only 10% of the total identified. In addition, the use of alternate terms of factors and the use of "critical success factors" and "success factors" are observed without a clear distinction.
CMMI Adoption and Retention Factors: A Systematic Literature Review
Keywords: Programas para computadoras--Control de procesos; Programas para computadoras--Mejoramiento; https://purl.org/pe-repo/ocde/ford#1.02.00